2021
DOI: 10.1016/j.clnu.2021.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Oral function in amyotrophic lateral sclerosis patients: A matched case–control study

Abstract: Background & aims: Patients with amyotrophic lateral sclerosis (ALS) develop swallowing difficulties with the progression of the disease. The present study aimed at comparing oral function and body composition between ALS patients and healthy controls, and at evaluating which parameters are the most discriminant between both groups. Methods: We included ALS patients at the start of their multidisciplinary follow-up at the Geneva University Hospitals and healthy age-, gender-, and dental status-matched adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
6
1
4
Order By: Relevance
“…Investigation of body composition may offer insights to address this issue. Previous studies with small sample sizes 18 , 19 found that ALS patients have a lower BMI and FFM than healthy controls, but no significant difference in body composition was found among patients and controls in this study. The inconsistent results might be explained by the different disease duration of patients and the demographic differences of controls.…”
Section: Discussioncontrasting
confidence: 87%
“…Investigation of body composition may offer insights to address this issue. Previous studies with small sample sizes 18 , 19 found that ALS patients have a lower BMI and FFM than healthy controls, but no significant difference in body composition was found among patients and controls in this study. The inconsistent results might be explained by the different disease duration of patients and the demographic differences of controls.…”
Section: Discussioncontrasting
confidence: 87%
“…Symptoms of genetic syndromes such as Down syndrome, or haematological and autoimmune diseases are often evident in the oro‐facial system as well. Further, a direct effect on the oral cavity was demonstrated for stroke and amyotrophic lateral sclerosis patients who lose much of their sensory and motor abilities and hence show impaired bolus control and swallowing disorders, leading to frequent feeding problems, low oral health–related quality of life and aspiration pneumonia 60,61 …”
Section: Aimmentioning
confidence: 99%
“…Nagely-Jalith Mejía-Chuquispuma 1,2,a , Ivo Luna-Mazzola 1,2,a , Laura Ricardina Ramírez-Sotelo 3,b Estimado Editor: La esclerosis lateral amiotrófica (ELA) es un trastorno neurodegenerativo que afecta las motoneuronas en la corteza motora, el tronco encefálico y la médula espinal (1). Si bien las manifestaciones clínicas de esta enfermedad son variadas y dependen del sitio de inicio de los síntomas, pueden causar parálisis muscular progresiva y ser de naturaleza terminal e invalidante (2).…”
unclassified
“…Si bien las manifestaciones clínicas de esta enfermedad son variadas y dependen del sitio de inicio de los síntomas, pueden causar parálisis muscular progresiva y ser de naturaleza terminal e invalidante (2). A pesar que la ELA tiene una incidencia global baja (1,9 a 4,5/100.000 personas por año) (3), los intentos por mejorar la calidad de vida de los pacientes que la padecen son muy valorados; por ello, en los últimos años se han realizado estudios con la finalidad de describir las manifestaciones orales generadas por esta enfermedad y cómo manejarlas (1)(2)(3)(4)(5). La presente carta tiene por objetivo justificar el rol del odontólogo como parte del equipo multidisciplinario para el manejo de pacientes con ELA.…”
unclassified
See 1 more Smart Citation